PERAN WANITA PADA INDUSTRI KECIL KERUPUK KEMPLANG DI KABUPATEN OGAN ILIR - Oktaviana Miftakhuljanah; Wahyu Budi Priatna; Suharno Suharno (School of Business, Bogor Agricultural University (SB-IPB), 2016)
One of the active roles of women is being able to assist the rural economy development starting from their family. Fish cracker is a small-scaled household industry that creates jobs and involves women who were previously just housewives in Ogan Ilir. To view and enhance the role of women, this study was conducted to analyze the role of the women in the fish cracker industry in Ogan Ilir and analyze the influence of the female characters on the business performance of this industry. As many as 30 women working in the cracker industry were selected as the samples. The analytical tool of PLS method was used to analyze the influence of the characters and to calculate the contribution of the role of the women using the proportion analysis. Revenues generated by the women from the fish cracker industry reached 38,46% indicating that they have a role in increasing their family income. PLS analysis results indicate that the individual character and psychological character have a positive impact on the business performance for the industry, increasing the revenues in the fish cracker business. The involvement of women in this industry can increase household incomes; furthermore, increased revenues can be generated by improving the quality of individuals through the related role of women.Keywords: role of women, fish cracker industry, revenue analysis, influence of character, PLS